Discrete element modelling of a flexible membrane for triaxial testing of granular material at high pressures - de Bono, John P.; McDowell, Glenn R.; Wanatowski, Dariusz (ICE Publishing, 2012)
The discrete element method (DEM) has been used to simulate triaxial tests on a bonded material at high pressures. A key feature of the model is the use of a flexible membrane that allows the correct volumetric deformation and the true failure mode to develop while applying constant confining pressure to the triaxial sample. The correct pattern of behaviour has been observed across a wide range of confining pressures, with both shear planes and barrelling failure being observed. The radial pressure applied by the membrane remains constant after large strains and deformation.